Litterfall and litter decomposition in area under restoration in the Cerrado - Calassa, Caio Henrique Januário; Ferreira, Jorge Luis; Pereira, Márcio Junior; Calil, Francine Neves; Silva-Neto, Carlos de Melo e (Revista Ecologia e Nutrição Florestal - ENFLO, 2023)
The litterfall is a very important component within a forest ecosystem, as it is responsible for the cycling of nutrients, in addition to indicating the productive capacity of the forest. The amount of litterfall varies according to the community and its successional stage. The different litterfall fractions have different structure and chemical composition and, therefore, decompose at different speeds. In view of this, the present study aimed to evaluate the contribution and decomposition of litter in an area of secondary vegetation undergoing restoration. An input of 33,941 kg ha-1 year-1 was observed, with the leaves compartment corresponding to the largest portion (69.68%), followed by branches (20.09%) and miscellaneous (10.22%). As for litter decomposition, a value for the decomposition constant K of 0.004227 g g-1 day-1 was found, and the half-life estimated at 164 days. The results found indicate a seasonal supply pattern, with peaks in the dry period, responding to the Cerrado’s climatic seasonality and a rapid return of nutrients to the soil.